Design of a lateral velocity observer based on synthesis of different sources. (September 2021) - Feng, Jianbo; Wang, Yanxue; Yang, Jianwei; Qi, Zhiquan
This paper is mainly devoted to estimating the lateral velocity of vehicle with an observer synthesis method using a cost-effective 6D inertial measurement unit. The four sources of observer to be synthesized come from the dynamics model, the kinematics model, and a LuGre tire model, respectively. The weight of each source is calculated by considering the nonlinear extent of each tire by means of the adaptation of tire cornering stiffness, which is adapted and updated using the dynamics model observer with the information obtained from the kinematics model observer. Then using the weighted sum of the four sources as the reference information for a modified kinematics observer, the final estimation can provide smooth and accurate results that are robust to sensor drifts and measurement noise, which is verified with several dSPACE based hardware-in-the-loop simulations.